Kontrowersje związane z reklamowaniem leków. Analiza porównawcza Polski i Stanów Zjednoczonych - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2016)
For many years, the subject of aggressive marketing campaigns conducted by pharmaceutical companies has been raised in Poland. Drug ads are everywhere, on television, the radio, magazines and on the Internet. Therefore, it is extremely important is to ensure both their legal and ethical dimension. In my article I will present the differences between direct-to-consumer advertising of medicines in Poland and in the US. The dissimilarities result mainly from differences in legislation. In Poland the law is much stricter than in the US. For example, in the United States companies are allowed to advertise prescription drugs directly to patients. In the whole of the European Union, and thus in Poland, it is strictly prohibited. The article will present other regulations existing in Poland and in the United States and it will compare them. It will show examples of violations of the law and ethics in the advertising of medicine in both countries. It will briefly outline the negative consequences of unacceptable pharmaceutical marketing.